Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.3390/rs70404442
|View full text |Cite
|
Sign up to set email alerts
|

L-Band SAR Backscatter Related to Forest Cover, Height and Aboveground Biomass at Multiple Spatial Scales across Denmark

Abstract: Mapping forest aboveground biomass (AGB) using satellite data is an important task, particularly for reporting of carbon stocks and changes under climate change legislation. It is known that AGB can be mapped using synthetic aperture radar (SAR), but relationships between AGB and radar backscatter may be confounded by variations in biophysical forest structure (density, height or cover fraction) and differences in the resolution of satellite and ground data. Here, we attempt to quantify the effect of these fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
38
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 72 publications
3
38
0
Order By: Relevance
“…4); an observation seen in the theoretical modelling of scattering regime transitions as larger stems and branches transition from Rayleigh to Mie/Optical scattering 26, 27 . Similarly, at high AGV ranges, an increase in forest height resulted in a negative AGV-backscatter trend; a similar negative trend is observed in numerous empirical studies 29, 30, 40–43 . The finding is also supported by the explanation that scattering is dominated by dense upper layers of canopy rather than deeper layers, hence decreasing trunk-ground double-bounce scattering 28 , particularly , and increasing signal extinction 25, 44 .…”
Section: Discussionsupporting
confidence: 82%
“…4); an observation seen in the theoretical modelling of scattering regime transitions as larger stems and branches transition from Rayleigh to Mie/Optical scattering 26, 27 . Similarly, at high AGV ranges, an increase in forest height resulted in a negative AGV-backscatter trend; a similar negative trend is observed in numerous empirical studies 29, 30, 40–43 . The finding is also supported by the explanation that scattering is dominated by dense upper layers of canopy rather than deeper layers, hence decreasing trunk-ground double-bounce scattering 28 , particularly , and increasing signal extinction 25, 44 .…”
Section: Discussionsupporting
confidence: 82%
“…Especially in tropical regions, cloud coverage is a reoccurring issue that aggravates monitoring based on multispectral satellite data. The extrapolating of accurate forest inventories or regional LiDAR-derived biomass estimations with large-scale satellite imagery represents an appropriate compromise [12][13][14][15]. Solberg et al [16] and Englhart et al [17] investigated the suitability of airborne laser scanning (ALS) for extrapolating biomass reference data from field plots.…”
Section: Introductionmentioning
confidence: 99%
“…[6]- [8] studies indicated that radar backscatter saturates when the level of biomass increases to a certain point. The saturation levels depend on the wavelengths (such as C, L, Pbands), polarization, incidence angle and the characteristics of vegetation stand structure and ground conditions.…”
Section: Introductionmentioning
confidence: 99%